Mixture of Garlic (Allium sativum) Extract 50% and Red Dragon Fruit (Hylocereus polyrhizus) peel 50% Effectiveness Against Enterococcus faecalis Bacteria - Christine; Fernanda, Bella; Florenly (Postgraduate, University of Mataram, 2025)
Enterococcus faecalis may infiltrate dentinal tubules in the cementum and dentin of the root, causing endodontic failure. A key stage in root canal therapy is irrigation. NaOCl is an efficient irrigation at higher concentrations, although its toxicity causes periapical tissue injury. Garlic and red dragon fruit peel suppress Enterococcus faecalis. To test the antibacterial activity of garlic (Allium sativum) extract and red dragon fruit (Hylocereus polyrhizus) peel extract at 50% against Enterococcus faecalis bacterium. A post-test only control-group design was used in this in vitro study. A 50% blend of garlic (Allium sativum) extract and red dragon fruit (Hylocereus polyrhizus) peel extract was compared to 2.5% NaOCl against Enterococcus faecali. ANOVA test results revealed significant differences (p < 0.05) in Enterococcus faecalis inhibition between garlic extract (Allium sativum), red dragon fruit peel extract, a mixture of both, and NaOCl: 9.30 ± 0.89, 15.88 ± 2.65, 12.30 ± 2.53, and 20.39 ± 2.41 mm. Red dragon fruit (Hylocereus polyrhizus) peel extract killed Enterococcus faecalis better than garlic (Allium sativum) and garlic-red dragon fruit peel combo.